Mechanistic and Pharmacological Evaluation of Cassia rhombifolia Fruit Extract in Murine Models of Pain, Fever, and Acute Inflammation - Tran, Thi Phuong Nhung; Vu, Thi Hoan; Nguyen, Thi Ngan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
This work investigated the pharmacological profile and dose-response behavior of an ethanol extract prepared from Cassia rhombifolia fruits (EECR) in mouse models of nociception, pyrexia, and short-term inflammatory reactions. Swiss albino mice were given EECR by mouth at 100, 200, or 300 mg/kg. Thermal pain thresholdswere evaluated using the hot plate and tail-flick paradigms. Yeast-induced hyperthermia was employed to assess antipyretic activity, and λ-carrageenan-evoked paw swelling served as an index of acute inflammation. Serum cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were assessed by enzyme-linked immunosorbent assay (ELISA). EECR significantly increased reaction latencies in both nociceptive paradigms and reduced fever and paw edema in a clear dose-related fashion (p < 0.01). At 300 mg/kg, the extract inhibited the tail-flick response by 83.27%, lowered hyperthermia by 68.42%, and diminished paw swelling by 64.25%. These functional benefits were accompanied by a marked suppression of pro-inflammatory mediators, and the EECR dose showed a pronounced negative relationship with cytokine levels (r = −0.98; p < 0.05). Across behavioral and biochemical outcomes, correlation coefficients and determination indices (R2) supported pronounced, almost linear dose-response patterns. Overall, the data indicate that EECR exerts potent pain-relieving, fever-lowering, and inflammation-attenuating effects in animal models and warrant further studies to isolate active principles, clarify molecular mechanisms, and evaluate its translational relevance.